Health Care Seeking Pattern among Out Patient Department (OPD) Patients in a Tertiary Care Chest Hospital, Dhaka (Chest & Heart Journal, 2023)
Introduction: South Asia has one quarter of the global population, but about half of the population live below the poverty line and has limited access to health care. Bangladesh is in the midst of an epidemiologic transition where the burden of disease is shifting from a disease profile dominated by infectious diseases to non-communicable disease. In this regard Chest Disease Hospitals specially in tertiary level are playing important role because both infectious chest diseases including PTB, pneumonia, COVID 19 infection and noncommunicable diseases like COPD, asthma, interstitial lung diseases are abundant among the general population.Aim of the study: The aim of this survey is to determine patients’ overall necessities which they expect from our hospital and to measure the level of satisfaction with quality of general services and specifically with staff attitude and hospital environment while receiving service in Outpatient department of tertiary level chest hospital like National Institute of Diseases of The Chest & Hospital (NIDCH), Mohakhali, Dhaka.Materials & Methodology: This prospective cross-sectional study was conducted in Outpatient department, National Institute of the Diseases of the Chest and Hospital (NIDCH), Mohakhali, Dhaka, Bangladesh from February 2021 to June 2021. Data were entered, checked and analyzed by SPSS for windows version 20.0 and MS Excel-2016.Results: This study was conducted among 357 patients. The mean age was 45.4±17.2 and the male female ratio was 1:0.5. Though NIDCH is situated in the city, 59.1% patient came from rural area and only 31.9% to came from urban area. Nearly half (49.6%) of the patients were from middle income society. Highest number (18.2%) was diagnosed as tuberculosis. Most common comorbid condition was DM (16.8%.). Most of the patients (56.9%) were satisfied with hospital OPD service.Conclusions: Most of the participants advised to increase the service points to reduce waiting time. The effectiveness of health care may determine to the satisfaction of patients with the health service provided.Chest Heart J. 2021; 45(2) : 57-70